Evaluation of Exotic parasitoid, Diglyphus isaea against Liriomyza trifolii on Tomato in Protected Cultivation in India - Sabir, Naved; Naved, Seema Hashim; Tanwar, R.K.; Singh, Balraj; Steinberg, Shimon; Adhikari, Susmita; Shrivastava, Arvind; Sindhu, S.S; kumar, Mukul; Bambawale, O.M. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Greenhouses in India are suffering from serious pest infestations mainly sucking pests and soil borne pathogens. As growers in India are largely dependent on insecticides and biorationals, commercial availability of bioagents is virtually negligible, thereby hampering ecofriendly objectives. A trial on evaluation of exotic parasitoid, Diglyphus isaea (Walker) (Hymenoptera: Eulophidae) against leaf miner, Liriomyza trifolii (Burgess) (Diptera) on tomatoes was conducted in a study plot of 150 m2  which was separated into two walk- in tunnels of 75 m2 each. The parasitoid was supplied by the commercial unit of Biobee Sde Eliyahu Ltd Israel. The trial included there treatments i.e. releases of D. isaea @ 0.5 wasps/m2 against leaf miner (T1), no pesticide application (T2) and management with chemical pesticides (T3). D. isaea was found effective in reducing the population of leaf miner significantly in tomato crop grown under protected structures.